ANALISA OUTLET PENGOLAHAN LIMBAH DI UNIT EFFLUENT TREATMENT PABRIK IIIB PT. PETROKIMIA GRESIK TERHADAP STANDAR BAKU MUTU LINGKUNGAN: ANALISA OUTLET PENGOLAHAN LIMBAH DI UNIT EFFLUENT TREATMENT PABRIK IIIB PT. PETROKIMIA GRESIK TERHADAP STANDAR BAKU MUTU LINGKUNGAN - Saputra, Ahmad Yusvani; Syarifah Haz, Dwi Faqihatus (Universitas Muhammadiyah Gresik, 2024)
Background: Solid, liquid and gas waste cause environmental pollution so that a waste treatment effort is needed to prevent environmental pollution. Environmental pollution occurs due to waste disposal that exceeds the Threshold Limit Value. Purpose: The purpose of this study is to analyze the effectiveness of the results of liquid waste management outlets with environmental quality standards. Methods: This research was conducted qualitatively using descriptive method. Liquid waste processing data collection is done through field observations, interviews, literature studies, and documentation. The data obtained is then discussed by comparing the Decree of the Minister of Environment and Forestry No. 175/Menlhk/Setjen/PKL.1/4/2017 Concerning Permits for Discharging Wastewater to the Sea. Results: In this study the results obtained were that the liquid waste treatment process in the Effluent Treatment unit had 2 stages (primary and secondary treatment) and the liquid waste processing outlets in the Effluent Treatment unit were not in accordance with the Quality Standards set by the company, which would then be accommodated in equalizer and will be reprocessed until the waste complies with existing environmental quality standards. Conclusion: The company has carried out liquid waste treatment so that it can prevent environmental pollution in accordance with the Decree of the Minister of Environment and Forestry No. 175/Menlhk/Setjen/PKL.1/4/2017 Concerning Permits for Disposing of Wastewater to the Sea, however, the output of liquid waste treatment outlets in the Effluent Treatment unit is not in accordance with the Quality Standards